Matrix-Assisted Bone Marrow Stimulation: A Surgical Technique - Christoph Lutter MD; Robert Lenz MD; Thomas Tischer MD, MBA (SAGE Publishing, 2021)
Background: Microfracture is an established technique for cartilage regeneration but is limited by many factors such as small defect size, intralesional osteophytes, and lower quality of cartilage regeneration. Therefore, methods to improve results after microfracture like additional matrix augmentation or autologous cell addition are promising techniques. An all-arthroscopic surgical technique for matrix-augmented bone marrow stimulation will be presented here. Indications: Cartilage lesions of moderate size (>1 cm 2 ) that appear too large or unsuitable for pure microfracture but do not yet meet the criteria for autologous cartilage transplantation (>2.5 cm 2 ). The exact size of suitable lesions is currently evolving with only few evidence-based data available. Technique Description: The arthroscopic procedure largely follows the standard microfracture technique. First, the cartilage defect is extensively debrided with removal of calcific cartilage layer. Stable cartilage margins have to be created with removal of all unstable fragments. The resulting well-defined defect is then measured with the use of a marking probe. The subchondral bone is then penetrated and opened using a microfracture awl. Next, the matrix based on hyaluronic acid (Hyalofast) is cut to the appropriate size. All joint fluid is removed, and the matrix is inserted through a previously placed canula and modeled into the defect with the probe. When the defect is well contained, no other fixation material is necessary. Otherwise, the matrix can be additionally fixed using fibrin clue. Cell application (dependent on regulatory issues) can be performed. Before closure, the joint should be moved to ensure safe fixation of the matrix. Results: Currently, there are only insufficient data to exactly define the defect size for microfracture or matrix-assisted bone marrow stimulation. Some studies show an advantage of using biomaterials compared with microfracture alone, but further studies are necessary. Discussion/Conclusion: The presented arthroscopic matrix-assisted bone marrow stimulation is a technically simple, inexpensive way of treating cartilage defects and should therefore be considered when treating affected patients. It can be used in a variety of joints. An additional combination with bone marrow-derived mesenchymal stem cells might be promising but is subject to country-specific regulatory issues.